EFEKTIVITAS PROGRAM BIMBINGAN BERBASIS EKSPRESIF ART THERAPY DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI ANAK USIA DINI - Wirastania, Aniek; Lathifah, Maghfirotul; Farid, Dimas Ardika Miftah; Pratiwi, Titin Indah; Lianawati, Ayong (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Communication is an effort to provide influence, inviting changes in thoughts and behavior so that they can follow the knowledge, understanding and actions of individuals. Communication skills are skills in establishing relationships between one individual and another individual in order to gain mutual benefits, both individually and in groups. This research aims to test the effectiveness of a guidance program based on expressive art therapy to improve communication skills in early childhood, namely Kindergarten A students at KB TK AL Mukmin Surabaya. The research method used in this research is quasi-experimental with a quantitative approach, pretest posttest one group research design. The instrument used in this research was an observation guide using purposive sampling technique. Furthermore, research subjects who had low communication skills were given treatment by implementing a guidance program based on expressive art therapy. The results of implementing this expressive art therapy-based guidance program can improve communication skills in early childhood. This condition can be seen from the difference between the pretest and posttest scores which show a significant difference.